Dynamic analysis of field-scale rockslides based on three-dimensional discontinuous smoothed particle hydrodynamics: A case study of Tangjiashan rockslide - Xia, Chengzhi; Shi, Zhenming; Liu, Maomao; Li, Bo; Yu, Songbo; Xue, Jianfeng (Engineering geology, 2024)
To improve the understanding of the dynamic disastrous process of field-scale rockslides, a novel numerical approach, Three-dimensional Discontinuous Smoothed Particle Hydrodynamics (3DSPH), was originally developed. This method comprehensively captures sequential stages of crack initiation and propagation, formation of contacts, frictional slip, catastrophic slides of rock masses, and final deposition, which was verified by three benchmark tests including the bouncing test of rigid balls, block sliding test and unconfined compression test of layered rock specimens. The approach was subsequently employed in the case of the Tangjiashan rockslide blocking valley event with particular attention paid to the influence of layered rock structure on the sliding and deposition processes. Field survey, geomorphological analysis and laboratory test of rock specimens were conducted to determine fundamental geological conditions and parameters required by the numerical simulation. Finally, 3D rockslide simulations with different rock layer thickness and strength subject to seismicity were conducted. The duration of the actual Tangjiashan rockslide's valley-blocking event (approximately 60 s) and the deposition area derived from the numerical simulation closely align with the field investigation. The rockslide mode is characterized by an ‘en masse’ motion with a peak sliding velocity of approximately 35–37 m/s. This single numerical code systematically elucidated the authentic attributes of the sliding process of large-scale rockslides, and realistically captured the characteristics of preservation of layered features within the sliding mass and ‘high-speed and short-distance’ movements with fluidization. These insights offer a fresh perspective for understanding the dynamics of large-scale rockslides with complex geological structures and subsequent accumulation processes. •A hybrid continuous and discontinuous method, 3DSPH, was originally developed for simulating rockslides.•3D modeling of Tangjiashan rockslide was implemented with particular attention paid to the effect of layered structure.•3DSPH realistically captured the characteristics of preservation of layered features within the sliding mass.